2014
DOI: 10.3899/jrheum.131027
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound of Synovitis in Rheumatoid Arthritis: Advantages of the Dorsal over the Palmar Approach to Finger Joints

Abstract: Although the dorsal approach detected fewer GSUS findings than the palmar approach, PDUS signals were significantly more frequently detected by dorsal US. In addition, the prevalence of double-positive joints with concurrent GSUS and PDUS findings was significantly higher with the dorsal approach. These data argue in favor of the dorsal US approach to finger joints in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 27 publications
2
13
0
1
Order By: Relevance
“…Probably the same explanation is valuable for the grade 1 synovitis, due to its incipient pathologic vascularization: in the presence of grade 1synovitis the PD signal was much frequent detected in the dorsal side (28.1%) comparing with palmar side (3.7%) [12]. Also, Witt et al [24] found in patients with newly diagnosed rheumatoid arthritis (RA) more pathologic findings in grey-scale US from the palmar approach and more frequent PD signals from the dorsal approach of the finger joints. In the study realized by Zufferey et al [25] the grade 1 PD signal was found only in 5% of normal volunteers (the authors did not specify the joints where this was found) and they considered to be relevant this grade of PD vascularization for the evaluation of remission in RA patients.…”
Section: Discussionmentioning
confidence: 88%
“…Probably the same explanation is valuable for the grade 1 synovitis, due to its incipient pathologic vascularization: in the presence of grade 1synovitis the PD signal was much frequent detected in the dorsal side (28.1%) comparing with palmar side (3.7%) [12]. Also, Witt et al [24] found in patients with newly diagnosed rheumatoid arthritis (RA) more pathologic findings in grey-scale US from the palmar approach and more frequent PD signals from the dorsal approach of the finger joints. In the study realized by Zufferey et al [25] the grade 1 PD signal was found only in 5% of normal volunteers (the authors did not specify the joints where this was found) and they considered to be relevant this grade of PD vascularization for the evaluation of remission in RA patients.…”
Section: Discussionmentioning
confidence: 88%
“…29 A study involving a cohort of 70 patients diagnosed with RA directly compared the dorsal and palmar approaches using PD-US, reporting greater prevalence of 22.1% versus 8.9% and greater double-positive rates, in which both grayscale US and PD-US are simultaneously observed, of 57.5% versus 17.4% for dorsal compared to palmar imaging of PIP joints. 30 Fluorescence tomographic imaging of injected contrast agent indocyanine green in inflamed fingers also concurs, revealing a greater degree of vascularization on the dorsal aspect. 31 This asymmetrical distribution of inflammation makes imaging orientation of joints using noncontact DOI systems of importance, the impact of which has not previously been investigated.…”
Section: Introductionmentioning
confidence: 84%
“…This is especially important when assessing erosive damage, but may also provide some additional information about the inflammatory load. However, applying a dorsal-only approach of the wrist and MCP/PIP/MTP joints, as in our candidate sets, increases feasibility and it has been shown that this projection captures most of the inflammatory findings 25. Also, the main objective of this study was to develop an US joint inflammation score, without focusing on evaluating erosive damage, thus the potential gain by applying several projections is not time efficient.…”
Section: Discussionmentioning
confidence: 99%